After Adam Smith : a Century of Transformation in Politics and Political Economy - Milgate, Murray; Stimson, Shannon C. (Princeton, New Jersey : Princeton University Press, 2009)
Few issues are more central to our present predicaments than the relationship between economics and politics. After Adam Smith looks at how politics and political economy were articulated and altered in the century following the publication of Smith's Wealth of Nations. It considers how grand ideas about the connections between individual liberty, free markets, and social and economic justice sometimes attributed to Smith are as much the product of gradual modifications and changes wrought by later writers. Thomas Robert Malthus, David Ricardo, James Mill, John Stuart Mill, and other liberals.
Introduction -- Adam Smith's political odyssey -- The rise and fall of civil society -- Economic life and political life -- The economic machine and the invisible hand -- The figure of Smith -- Population and political economy -- Utility, property, and political participation -- Economic opinion on parliamentary reform -- Utopias and stationary states -- Labour defended -- Individual liberty and the liberty of trade -- Two critiques of classical political economy.
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Economics -- Political aspects -- History; Classical school of economics -- History; Économie politique et politique -- Histoire; École classique d'économie politique -- Histoire; BUSINESS & ECONOMICS -- Industries -- General; Classical school of economics; Economics -- Political aspects; Klassische Nationalökonomie; Politik; Politische Ökonomie; Wirtschaft; Wirtschaftswissenschaften; History